2021
DOI: 10.1177/15248380211036063
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and Intimate Partner Violence Perpetration in Undergraduate Samples: A Review of the Literature

Abstract: Intimate partner violence (IPV) perpetration increases throughout young adulthood and is particularly widespread among college students, resulting in mental health and academic consequences. Deficits in emotion regulation (ER) are an important factor associated with IPV perpetration; the developmental tasks and challenges associated with college, including relationship stressors and hazardous alcohol use, implicate ER as a particularly relevant risk factor for IPV perpetration. Thus, college presents an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 85 publications
3
18
0
Order By: Relevance
“…Specifically, there were significant declines of about 50% in psychological IPA from baseline to 6-month follow-up for women in the treatment condition, whereas there were no changes for women in the control condition. These findings are in line with theoretical approaches (e.g., I 3 Model; Finkel, 2014;Finkel & Eckhardt, 2013;Slotter & Finkel, 2011) and prior research (e.g., Fruzzetti & Levensky, 2000;Neilson et al, 2021;Stappenbeck, Davis, et al, 2016;Waltz, 2003) linking the current treatment targets (alcohol use, ER, and distress tolerance) and IPA. In fact, a prior evaluation of this intervention (see Stappenbeck et al, 2021) showed a reduction in heavy drinking and improvements in ER and distress tolerance skills.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, there were significant declines of about 50% in psychological IPA from baseline to 6-month follow-up for women in the treatment condition, whereas there were no changes for women in the control condition. These findings are in line with theoretical approaches (e.g., I 3 Model; Finkel, 2014;Finkel & Eckhardt, 2013;Slotter & Finkel, 2011) and prior research (e.g., Fruzzetti & Levensky, 2000;Neilson et al, 2021;Stappenbeck, Davis, et al, 2016;Waltz, 2003) linking the current treatment targets (alcohol use, ER, and distress tolerance) and IPA. In fact, a prior evaluation of this intervention (see Stappenbeck et al, 2021) showed a reduction in heavy drinking and improvements in ER and distress tolerance skills.…”
Section: Discussionsupporting
confidence: 89%
“…The ability to access and use one’s inhibitory capabilities is impacted by disinhibitory factors , including heavy drinking. Emotion regulation (ER) has emerged as an inhibitory factor, with ER deficits consistently and robustly associated with IPA, particularly in the context of other risk factors for IPA such as heavy drinking (Neilson et al, 2021). Indeed, ER difficulties have been shown to moderate the association between heavy drinking and IPA such that the positive relation between heavy drinking and IPA was stronger for those with greater impulse control difficulties and more limited access to ER strategies (Stappenbeck, Davis, et al, 2016).…”
Section: The Present Studymentioning
confidence: 99%
“…The findings regarding psychological IPA likelihood are in line with theoretical approaches (e.g., Finkel, 2011Finkel, , 2014Finkel & Eckhardt, 2013) and prior research (e.g., Neilson et al, 2023) linking emotional clarity and IPA. Using the CR skills taught in the intervention may have helped men in effectively overcoming aggressive urges due to improved ability to clarify what they were feeling, thereby resulting in decreased psychological IPA likelihood following the intervention.…”
Section: Discussionsupporting
confidence: 87%
“…Although participants were not selected based on a history of IPA, there are findings showing that individuals who perpetrate one form of aggression are likely to perpetrate multiple forms (Wilkins et al, 2014). Given known associations between CR, emotional clarity, and IPA (Neilson et al, 2023), the goal of this study was to preliminarily examine whether the intervention would also be helpful in reducing the likelihood of IPA through bolstered inhibition. Specifically, as suggested by the I 3 Model, we hypothesized that improved CR abilities would increase men's emotional clarity, thereby decreasing their likelihood of perpetrating IPA due to better control of aggressive urges.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation